2015
DOI: 10.1177/2158244015572488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Suppressing Thoughts of Desire to Smoke on Ratings of Desire to Smoke and Tobacco Withdrawal Symptoms

Abstract: Studies indicate that while suppressing smoking thoughts increases subsequent smoking, it may have no impact on desire to smoke. However, previous research has examined suppression of general smoking thoughts rather than thoughts specifically related to desire to smoke. The present study investigated whether suppression of thoughts of desire to smoke results in subsequently elevated ratings of desire to smoke. An experimental study examined the effects of suppressing thoughts of desire to smoke, versus express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…This can be seen as consistent with research on mindfulness, commonly defined as “the state of being attentive to, and aware of, what is taking place in the present” (Brown & Ryan, 2003, p. 822). Previous research has shown positive associations between mindfulness and well-being, beneficial effects of mindfulness training on mental health (e.g., see Brown & Ryan, 2003, for a review), and negative correlations between mindfulness and thought suppression (e.g., Baar, Smith, Hopkins, Krietemeyer, & Toney, 2006; Erskine, Rawaf, Grice & Ussher, 2015; Erskine, Ussher, Cropley, Elgindi, Zaman & Corlett, 2012). …”
Section: Studymentioning
confidence: 99%
“…This can be seen as consistent with research on mindfulness, commonly defined as “the state of being attentive to, and aware of, what is taking place in the present” (Brown & Ryan, 2003, p. 822). Previous research has shown positive associations between mindfulness and well-being, beneficial effects of mindfulness training on mental health (e.g., see Brown & Ryan, 2003, for a review), and negative correlations between mindfulness and thought suppression (e.g., Baar, Smith, Hopkins, Krietemeyer, & Toney, 2006; Erskine, Rawaf, Grice & Ussher, 2015; Erskine, Ussher, Cropley, Elgindi, Zaman & Corlett, 2012). …”
Section: Studymentioning
confidence: 99%
“…The other associated variables were included for the following reasons. Firstly research has indicated that dispositional mindfulness and the use of thought suppression are negatively correlated, meaning that more mindful individuals report using thought suppression less frequently (see Erskine, Ussher, Cropley, Elgindi, Zaman, & Corlett, 2012;Erskine, Rawaf, Grice, & Ussher, 2015). Secondly, as individuals often improve on a domain with repeated practice (Logan, & Klapp, 1991) the extent to which one reports intrusions during active suppression may be linked to how frequently one uses thought suppression in everyday life.…”
Section: Ageing and Intrusive Thoughtsmentioning
confidence: 99%